1986
DOI: 10.1523/jneurosci.06-06-01822.1986
|View full text |Cite
|
Sign up to set email alerts
|

Central projections of identified Drosophila sensory neurons in relation to their time of development

Abstract: Eight sensory structures (campaniform sensilla), appearing identical in the light and scanning electron microscopes, are found in specific locations on the wings of Drosophiia. Their axons enter one of 2 central tracts, a medial one or a lateral one. The topographic arrangement of the sensilla on the wing is not reflected in this central projection pattern. There is, however, a strict correlation between the time when a sensillum develops and the path its axon follows: The 4 sensilla whose axons form the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 23 publications
(41 reference statements)
3
51
0
Order By: Relevance
“…Axons from different classes could also project to specific layers that are prepatterned by the processes of target interneurons or by other axons. Finally, the projection of da axons to different layers could conceivably reflect a temporal order of sensory axon arrival in the CNS, similar to the three-way correlation between mediolateral axon position, physiological function and time of differentiation among Drosophila wing campaniform sensilla (Palka et al, 1986). Among the ventral cluster da neurons, a group with differentiation that has been examined in the greatest detail, the class II neurons appear to be the first-born, followed by class III neurons and class IV neurons (Orgogozo et al, 2001).…”
Section: Discussionmentioning
confidence: 94%
“…Axons from different classes could also project to specific layers that are prepatterned by the processes of target interneurons or by other axons. Finally, the projection of da axons to different layers could conceivably reflect a temporal order of sensory axon arrival in the CNS, similar to the three-way correlation between mediolateral axon position, physiological function and time of differentiation among Drosophila wing campaniform sensilla (Palka et al, 1986). Among the ventral cluster da neurons, a group with differentiation that has been examined in the greatest detail, the class II neurons appear to be the first-born, followed by class III neurons and class IV neurons (Orgogozo et al, 2001).…”
Section: Discussionmentioning
confidence: 94%
“…S2). In adult flies, tmc-Gal4 labeled subsets of neurons in the mouth parts, olfactory neurons in the antenna (38), wing bristle neurons (39), haltere neurons (40), arista neurons (41), and many other sensory neurons (Fig. S2), including a subset of chordotonal (Cho) neurons (42), the hearing neurons of the fly (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such strategy is not likely to be unique to the lateral line, however. For example, mechanosensory neurons of the wing or photoreceptor neuron of the eye in Drosophila also produce tiered central projections based on their time of development (Palka et al, 1986;Morey et al, 2008;Petrovic and Hummel, 2008). Earlier studies in Xenopus tested the involvement of timing in generating the topographic organization of the neuronal projection from the retina to the tectum, and concluded that it likely plays a permissive rather than an instructive role in axonal organization (Holt, 1984).…”
Section: Discussionmentioning
confidence: 99%